Initial strategies for integrating buprenorphine into HIV care settings in the United States. - Sullivan, Lynn E; Bruce, Robert D; Haltiwanger, David; Lucas, Gregory M; Eldred, Lois; Finkelstein, Ruth; Fiellin, David A (Clinical infectious diseases : an official publication of the Infectious Diseases Society of America, 2006)
The Centers for Disease Control and Prevention's HIV Prevention Strategic Plan Through 2005 advocated for increasing the proportion of persons with human immunodeficiency virus (HIV) infection and in need of substance abuse treatment who are successfully linked to services for these 2 conditions. There is evidence that integrating care for HIV infection and substance abuse optimizes outcomes for patients with both disorders. Buprenorphine, a recently approved medication for the treatment of opioid dependence in physicians' offices, provides the opportunity to integrate the treatment of HIV infection and substance abuse in one clinical setting, yet little information exists on the models of care that will most successfully facilitate this integration. To promote the uptake of this type of integrated care, the current review provides a description of 4 recently implemented models for combining buprenorphine treatment with HIV primary care: (1) an on-site addiction/HIV specialist treatment model; (2) a HIV primary care physician model; (3) a nonphysician health professional model; and (4) a community outreach model.
Keywords: Antiretroviral Therapy, Highly Active; Buprenorphine; Centers for Disease Control and Prevention (U.S.); Delivery of Health Care, Integrated; Female; Health Resources; Health Services Needs and Demand; HIV Infections; Humans; Male; Methadone; Naloxone; Narcotic Antagonists; Opioid-Related Disorders; Patient Selection; Primary Health Care; Program Evaluation; Risk Assessment; Substance Abuse Treatment Centers; United States